The Constitutionality of Simultaneous Elections in The Constitutional Court Decision Number 135/PUU-XXII/2024 and its Implications for Democracy in Indonesia - Safitri, Dewi Sekar Ayu; Zalil, Muhammad Abdul; Hadi, Abdul (Rechtsvinding, 2025)
General elections, as the primary means of exercising popular sovereignty, form a vital pillar of Indonesia’s constitutional democracy. The Constitutional Court Decision No. 135/PUU-XXII/2024, submitted by the Perludem Foundation, marks a critical judicial review of the constitutionality of the five-box simultaneous election model used in 2019 and 2024. This study aims to examine whether the system aligns with the principles of convenience, fairness, and legal certainty mandated by the 1945 Constitution, and how the Court’s decision redefines electoral design in Indonesia. Employing a normative juridical approach combined with case and conceptual analysis, the research focuses on constitutional provisions and relevant electoral laws. The findings reveal that the five-box model undermines the effective exercise of popular sovereignty, weakens political party institutionalization, and disregards the Constitutional Court’s prior guidance on electoral simultaneity. Consequently, the study proposes a new framework dividing elections into national and local stages, held at separate intervals to enhance manageability and voter participation. The results underscore the Constitutional Court’s role as the guardian of the Constitution in correcting electoral practices that deviate from democratic principles. It concludes that legislative follow-up through simpler and more participatory regulations is imperative to ensure the integrity and sustainability of Indonesia’s democratic process.